TRANSFUSION-RELATED ACUTE LUNG INJURY IN A PEDIATRIC INTENSIVE CARE UNIT OF PAKISTAN - Jamil, Muhammad Tariq; Dhanani, Zehra Nizar; Abbas, Qalab; Jurair, Humaira; Mahar, Farheen Karim; Haque, Anwarul (Journal of Ayub Medical College Abbottabad, 2017)
Background: Transfusion-Related Acute Lung Injury (TRALI) is a major cause of transfusion-related morbidity and mortality in the intensive care unit setting. There is a paucity of such data from Pakistan. The purpose of this study is to assess the incidence and outcome of TRALI in critically ill children admitted in a pediatric intensive care unit (PICU) of Pakistan. Methods: This is a retrospective cohort study of all critically ill or injured children who developed TRALI or possible TRALI after blood transfusion based on Canadian Conference Consensus criteria in a closed multidisciplinary-cardiothoracic PICU from January 2012 to June 2016. The demographic, pertinent clinical data, transfusion-related variables and outcome of all cases of TRALI were recorded. Results: Of total 2975 admissions in the PICU during study period, 35.8% (1066) received 5124 blood components. Eleven cases developed TRALI in our cohort. The incidence of TRALI was 1.03% per patient transfused and 0.19% (19/100,000 per blood product transfused). Median age was 8 (range 1-14) yr., 70 % (n=8) were male. Mean PRISM-III score was 16.3±6.7. Mean time interval for onset of TRALI was 2.73±1.67 hr. The postoperative cardiac surgical and hematology-oncology patients were most common categories (63.6%). Plasma and platelets were the most commomly identified trigger of TRALI. The case-specific mortality was 63.6% and the overall mortality was 10.7% (p<0.0001). Conclusion: The incidence of TRALI in critically ill children is low, but is associated with high mortality. Critically ill children with high PRISM-III score, postoperative cardiac surgical and hematology-oncology patients are often affected by TRALI. Keywords: transfusion, critically ill child, TRALI, outcome, incidence, Acute Lung Injury